ChemInform Abstract: Biomacromolecules as Novel Green Flame Retardant Systems for Textiles: An Overview. Issue 2 (January 2015) - Malucelli, Giulio; Bosco, Francesca; Alongi, Jenny; Carosio, Federico; Di Blasio, Alessandro; Mollea, Chiara; Cuttica, Fabio; Casale, Annalisa
Abstract Review: 86 refs.